Fabrication of face cream containing enriched fraction of protocatechuic acid from Clinacanthus nutans (C. Nutans) leaves - Zamery, Muhammad 'Izzuddin; Ab. Hadi, Hazrina (Malaysian Pharmaceutical Society, 2017)
INTRODUCTION: C. nutans is predominantly native to Malaysia and contains variety of bioactive constituents including protocatechuic acid (PCA). PCA was found to have cosmeceutical value which protects skin from oxidative stress. Emulsion is a dispersion of a liquid in other immiscible liquid with surfactant as stabilizer. Most cosmetics developed as oil-in-water emulsion and required to have certain criteria such as homogenous, mild-to-skin and stable. OBJECTIVES: To formulate and characterise a face cream containing PCA enriched fraction. METHODS: Cream formulation involves 82.7% aqueous and 15% oil and 2.3% cooling phases. It was formulated via double boiling, agitation and homogenization techniques. Formulated cream was characterised by evaluating physical (phase separation before and after centrifugation), organoleptic (visual, colour, odour and texture), particle size, zeta potential, rheology, pH and microbial contamination and PCA quantification by high-performance liquid chromatography (HPLC) analyses. RESULTS: A homogenous cream was formulated having light yellow colour, smooth texture and chamomile scent. Centrifugation test showed no phase separation. Particle size of the cream was 4.27±0.05µm with the span value of 0.55±0.02. Zeta potential of the cream was -68.3±0.8mV. The rheological analysis of the cream showed flow behaviour of pseudoplastic non-newtonian. Then, pH of the cream was 5.14±0.02. All microbial limit test showed absent of microbial growth. HPLC analysis showed the PCA peak clearly at 8.122 minutes retention time. CONCLUSION: Face cream containing PCA enriched fraction from C. nutans leaves was formulated. The parameters for cream characterization were within the specification.